The Relationship of Religious Moderation of The Malay Islamic Community of South Sumatra to Democratic Stability - Hilmin Hilmin; Muhammad Adil; Dwi Noviani; Mustafiyanti Mustafiyanti (The International Conference on Education, Social Sciences and Technology (ICESST), 2023)
This research entitled "The Relation of Religious Moderation in the Malay Muslim Community of South Sumatra to Democratic Stability" aims to analyze the relationship of religious moderation in the Malay Muslim community in South Sumatra and its impact on democratic stability in the region. In the context of a religiously and ethnically heterogeneous society, religious moderation is an important factor influencing the stability of a democratic system. This research methodology includes surveys, interviews and content analysis regarding the understanding and practice of religious moderation in the Malay Muslim community. The resulting data was then analyzed to determine the relationship between religious moderation and democratic stability, taking into account other factors that might influence this relationship. Research findings show that in the Malay Muslim community in South Sumatra, the practice of religious moderation can make a positive contribution to democratic stability. Religious moderation can play an important role in encouraging interfaith dialogue, reducing opportunities for conflict, and increasing inclusive political participation. In this context, understanding and implementing the values ​​of religious moderation in the Malay Muslim community of South Sumatra can be considered as social capital that supports sustainable and stable democratic development. These results have important implications for developing policies and strategic approaches that encourage religious moderation as an integral part of the social and political dynamics of society.